(3OGYi GdadGM Edi SHjd GdfLGMs - (3eMeO Hf eMeO Rjf GdYGHOjf GdCTYQj GdZeQj SHW GdeQUaj , Rjf GdYGHOjf,J (B966 (3g` s ((3YHO GdcQje Hf Ydi GdTfHGHi GdLjRGhi s)
(3ChdgG (B:s
(3jbhd GdabjQ Edi Yah Gddg hdWag GdNai eMeO GdeOYh Rjf GdYGHOjf GdYeQi SHW GdYGQa GdLdjd Ydi Hf Ndjd GdeQUai CYGO Gddg Ydi hYdi GdeSdejf ef HQcGJg GdMeO ddg GdPi BJi ChdjGAg ef dOfg YdekG CeG HYO abO SCdJfi CjgG GdSGFd Yf GdRgO gd gh Qs
(3BNQgG (B:s
(3hMci Yf CHj YHO Gddg Hf Najb Cfg bGd QCjJ GdfHi Udi Gddg Ydjg hSde ai GdefGe abGd di ef YQa WQjbkG Edi Gddg jScdg Ke QLY Yfg YPHg Gddg gPG BNQ eG CQGO EjQGOg SjOfG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B58 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B257 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B246s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B728s
Keywords: (3GdJUha hGdBOGH GdTQYjIs